Optimization of the Intelligence Gathering Performance of Unit 4 Intelligence and Security Unit Sragen Resort Police to Countermeasures Radicalism - Adlan, Muhammad Kafin (Indonesian Journal of Police Studies, 2024)
The focus of research in this Final Project is optimizing the performance of intelligence gathering Units 4 Intelligence and Security unit (“Satintelkam”) Sragen Resort Police to overcome radicalism, this is considered important because of the rampant cases of radicalism that occur   in Sragen County.  This study aims to describe the Organizational Resources and management of the implementation of the intelligence gathering Units 4 Satintelkam unit Sragen Resort Police.  The concepts and theories used are management theory, Organizational Resources theory, competency theory, SWOT analysis, optimization concept, performance concept, shipbuilding concept, concept countermeasures, and the concept of radicalism.  In this study, a qualitative approach with a descriptive method of analysis was used. The research data was obtained through interviews, document studies and observations, then triangulated the data to obtain valid data. The results of this study are: (1) Organizational resources that have not been supported to carry out ideal intelligence gathering in accordance with applicable standard operating procedure (SOP) and regulations; (2) Bad management of the intelligence gathering and not in accordance with applicable SOP and regulations.  The conclusions of this final project are: (1) the quality and performance of the intelligence gathering must be improved and also collaborate with other agencies to overcome the shortcomings of Organizational Resources; (2) Management of the intelligence gathering   must be optimized by means of implementation training according to SOP and also better supervision of the implementation of duties from leaders to members.